2007
DOI: 10.1073/pnas.0610456104
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Syntrophus aciditrophicus : Life at the thermodynamic limit of microbial growth

Abstract: Biochemically, the syntrophic bacteria constitute the missing link in our understanding of anaerobic flow of carbon in the biosphere. The completed genome sequence of Syntrophus aciditrophicus SB, a model fatty acid-and aromatic acid-degrading syntrophic bacterium, provides a glimpse of the composition and architecture of the electron transfer and energy-transducing systems needed to exist on marginal energy economies of a syntrophic lifestyle. The genome contains 3,179,300 base pairs and 3,169 genes where 1,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
277
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(289 citation statements)
references
References 46 publications
11
277
0
1
Order By: Relevance
“…Examining the TA decarboxylase data set did not show any clear homologs of the Thauera BCRs. Instead, homologs are found in the alternative BCRindependent mechanism within a set of 44 genes that have been postulated to operate in Geobacter metallireducens and 'Syntrophus aciditrophicus' (Butler et al, 2007;McInerney et al, 2007;Peters et al, 2007). The key BCR enzyme in G. metallireducens was successfully characterized in vitro (Kung et al, 2009).…”
Section: Pelotomaculummentioning
confidence: 99%
“…Examining the TA decarboxylase data set did not show any clear homologs of the Thauera BCRs. Instead, homologs are found in the alternative BCRindependent mechanism within a set of 44 genes that have been postulated to operate in Geobacter metallireducens and 'Syntrophus aciditrophicus' (Butler et al, 2007;McInerney et al, 2007;Peters et al, 2007). The key BCR enzyme in G. metallireducens was successfully characterized in vitro (Kung et al, 2009).…”
Section: Pelotomaculummentioning
confidence: 99%
“…The predicted beta-subunit of at least one of the putative acetyl-CoA synthetases contained a conserved histidine residue typical of well characterised acetyl-CoA synthetases that specifically form acetate and differentiate them from other structurally related succinyl-CoA synthetases (Bräsen et al, 2008). DEH-J10 may therefore gain ATP by substrate-level phosphorylation during the conversion of acetyl-CoA to acetate (McInerney et al, 2007;Bräsen et al, 2008).…”
Section: Acetyl-coa Synthetasesmentioning
confidence: 99%
“…We identify diverse Pelotomaculum (bins TAPelo1-TAPelo4) predominate the community, accounting for 16.8% and 31.7% of the bacterial community and metratranscriptome. These Pelotomaculum indeed encode and express genes for syntrophic energy conservation (Hdr-Ifo and ECHyd) and a previously observed pathway for TA degradation to acetate, CO 2 and H 2 (Figure 2 and Supplementary Table S4) (McInerney et al, 2007;Lykidis et al, 2011). In addition, we newly identify expression of a clostridial electron-bifurcating butyryl-CoA dehydrogenase in TAPelo3 that may facilitate the previously hypothesized Sporotomaculum-like energy-conserving butyrate generation from aromatic compound degradation (Qiu et al, 2003;Buckel and Thauer, 2013;Wu et al, 2013;Nobu et al, 2014), albeit refuting the involvement of previously identified non-energy-conserving acylCoA dehydrogenase (Lykidis et al, 2011;Wu et al, 2013).…”
Section: Metatranscriptomicsmentioning
confidence: 99%
“…Based on the known metabolic diversity of methanogenic environments (Schink, 1997;McInerney et al, 2009), uncultivated secondary degraders and scavengers must perform fermentative, syntrophic or acetogenic metabolism. To investigate the ecological roles and metabolic capabilities of the uncultivated taxa, this study used an 'ecogenomics' approach synthesizing single-cell genomics (Marcy et al, 2007), metagenomics (Tyson et al, 2004), metatranscriptomics (Frias-Lopez et al, 2008) and metabolic reconstruction assisted by comparative genomics of acetogen and syntroph energy conservation pathways (McInerney et al, 2007;Muller et al, 2008;Sieber et al, 2010Sieber et al, , 2012Nobu et al, 2014). In doing so, we provide the first look into the genomes and metabolism of many uncultivated taxa and propose how these organisms metabolically interact to achieve holistic carbon flux from TA to CH 4 and CO 2 in the methanogenic reactor.…”
Section: Introductionmentioning
confidence: 99%